Efficient Data Integrity and Auditing in Cloud by using Block Chain (International Journal of Innovative Research in Computer Science & Technology, 2020)
The main aim of this paper is to discuss the  usage of cloud storage services, enabling individuals to store  their information in the cloud and keep away from the local  data storage and maintenance expense. Numerous data  integrity auditing systems have been implemented to  guarantee the quality of the data stored in the cloud. An  individual would like to enroll his private key to create the  authenticators for understanding the auditing of data  integrity in certain, but not all of the current system. The  user must then have a hardware token (e.g. USB token,  smart card) for storing the private key and memorizing a  password to trigger the private key. Most of the new data  integrity auditing system will be unable to operate if the user  misplaced this hardware token or forgot this password. We  are proposing a new module called data integrity auditing  without private key storage to solve this issue, and  developing such a scheme using block chain technology. In  this project we are proposing a computerized signature  along with face reorganization with block chain operation,  so that there will be no unique design to obtain unauthorized  and furthermore to prevent hacking operation and all the  respective user data or information will be stored in cloud  with maximum security.
Keywords: Cloud storage; Data integrity auditing and Data security Biometric data